Ethical Cosmetology as a Vector of Public Health: Justification of the National Importance of Non-Invasive Practices - Melnyk, Larysa (Global Prosperity, 2025)
Abstract. Against the background of the growing psycho-emotional vulnerability of the population and the need for safe approaches to appearance care, non-invasive aesthetic methods are gaining particular importance. They are considered an ethically justified and socially acceptable alternative to invasive interventions. The purpose of the study is to substantiate the national importance of the spread of non-aggressive procedures as a safe alternative to invasive interventions. Materials and methods. The study used the method of systematic literature review in accordance with the requirements of PRISMA. Scientific publications from 2019–2025 were analyzed, from the scientometric databases PubMed, Scopus and Web of Science. Results. Data analysis shows an increase in the frequency of non-invasive procedures from 58% in 2020 to a projected 74% in 2024. Statistical and clinical data confirm higher levels of customer satisfaction, lower levels of side effects and a significant reduction in psychological distress scores comparable to the results of invasive interventions. Non-invasive aesthetic cosmetology is considered as a component of a preventive model of public health, with possible integration into social and rehabilitation programs for vulnerable groups of the population. The work emphasized the need for ethical rethinking of beauty practices and patient expectations. Conclusions. Non-invasive aesthetic practices have proven their effectiveness, safety and psychological acceptability, which justifies their importance for modern ethical cosmetology and public health.